2005
DOI: 10.1007/s00394-005-0572-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cranberry juice consumption on antioxidant status and biomarkers relating to heart disease and cancer in healthy human volunteers

Abstract: Cranberry juice consumption did not alter blood or cellular antioxidant status or several biomarkers of lipid status pertinent to heart disease. Similarly, cranberry juice had no effect on basal or induced oxidative DNA damage. These results show the importance of distinguishing between the in vitro and in vivo antioxidant activities of dietary anthocyanins in relation to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
232
7
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(260 citation statements)
references
References 62 publications
18
232
7
3
Order By: Relevance
“…42 Human intervention studies using berries (either fresh, as juice, or freeze-dried), or purified anthocyanin extracts have demonstrated significant improvements in antioxidant activities, including lowdensity lipoprotein oxidation and lipid peroxidation. 43,44 These benefits were recognized in healthy subjects as well as in those with existing metabolic risk factors. It has been suggested that underlying mechanisms of these beneficial effects include upregulation of endothelial NO synthase, decreased activities of carbohydrate-digestive enzymes, decreased oxidative stress, and inhibition of inflammatory gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…42 Human intervention studies using berries (either fresh, as juice, or freeze-dried), or purified anthocyanin extracts have demonstrated significant improvements in antioxidant activities, including lowdensity lipoprotein oxidation and lipid peroxidation. 43,44 These benefits were recognized in healthy subjects as well as in those with existing metabolic risk factors. It has been suggested that underlying mechanisms of these beneficial effects include upregulation of endothelial NO synthase, decreased activities of carbohydrate-digestive enzymes, decreased oxidative stress, and inhibition of inflammatory gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectum, azoxymethane-treated rats [20] Colorectum, azoxymethane-treated rats [21] Colorectum, azoxymethane-treated rats [44] Colorectum, DMH-and PhIP-treated rats [18] Freeze-dried black raspberries Healthy volunteers [70] Healthy volunteers [71] Healthy volunteers [72] Healthy volunteers [73] Healthy …”
Section: Conflict Of Interest Disclosures: Nonementioning
confidence: 99%
“…There is some evidence from epidemiological studies that suggests a higher consumption of anthocyanin-rich foods is associated with a reduced risk for cardiovascular disease [8,9]. However, intervention studies do not always support these findings [10]. In the case of blood pressure, plausible mechanisms from experimental studies include their effects on vascular blood flow and flow-mediated dilation (FMD) [11,12].…”
Section: Introductionmentioning
confidence: 99%